Aspek Hukum Perjanjian Kerja Dalam Proyek Bangunan - Arkam Laya (Universitas Negeri Gorontalo, 2009)
Generally, implementation of a development project requires law peripheral in the form of agreement. Agreement is important to give a legal fundament in activity to finalizing building project till finish. Basically, every party involving in an implementation of construction contract is main party that have signing up construction, that is bath of employer and developer ones. To be able to the happening of contractual terms between construction service feeders and construction service user hence they must bind itself in an agreement based on principle of agreement reached. Kata Kunci: Hukum, Perjanjian, Proyek, Bangunan, Kesepakatan